Bond behavior of Flax-FRCM and PBO-FRCM composites applied on clay bricks: Experimental and theoretical study. (20th June 2016) - Olivito, Renato S.; Codispoti, Rosamaria; Cevallos, Oscar A.
Abstract: In this paper an experimental investigation on bond adhesion between sustainable composite material and masonry support was carried out in the Civil Engineering Laboratory of the University of Calabria. This topic was addressed performing experimental tests and considering a theoretical approach. For this purpose, double-lap shear bond tests were carried out on typical masonry clay bricks, externally strengthened with composite materials (NFRCM – Natural Fibers Reinforced Cementitious Matrix). In particular, two different composite materials were studied: flax fabric-reinforced cementitious matrix (Flax-FRCM) and PBO fabric-reinforced cementitious matrix (PBO-FRCM) composites. In the end, a comparison between the experimental results achieved and those proposed by the Italian design code CNR 200 R1/2012 was performed, picking out some relevant aspects of the design procedures.